CONSUMER BEHAVIOR: SHOPPING ENJOYMENT AND SOCIAL INFLUENCE ON PURCHASE INTENTION - Haryanti, Intisari (JURNAL DIMENSI, 2025)
This study aims to examine the influence of shopping enjoyment and social influence on consumers' purchase intention. Shopping enjoyment, defined as the pleasure derived from the shopping experience, has been shown to positively affect consumers' impulse buying and purchase motivation. Social influence, which encompasses the opinions, behaviors, and expectations of others, plays a significant role in shaping consumer decisions, especially in the context of modern digital and social commerce platforms. Using a quantitative approach with survey data collected from online and offline shoppers, the research tests the direct effects of shopping enjoyment and social influence on purchase intention, as well as the mediating roles of impulse buying tendencies. The findings reveal that both shopping enjoyment and social influence have significant positive impacts on purchase intention, suggesting that marketers should emphasize creating enjoyable shopping experiences and leverage social proof to enhance consumer engagement. This study contributes to consumer behavior literature by integrating hedonic and social factors, providing practical insights for retail and e-commerce strategies to increase sales and customer loyalty.